Upaya Meningkatkan Hasil Belajar IPS dengan Pembelajaran Kooperatif Tipe NHT dan Pemanfaatan Media Gambar pada Siswa Kelas VI Semester II UPT SDN 1 Palapa Bandar Lampung Tahun Pelajaran 2022/2023 - Relyse, Relyse (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2023)
The purpose of this study was to improve social studies learning outcomes with NHT type cooperative learning and the use of image media in grade VI UPT SDN 1 Palapa students. The benefits that can be obtained from this research are as a useful contribution to improve social studies learning outcomes class VI UPT SDN 1 Palapa. This study is a class action research consisting of 2 cycles. Each cycle consists of planning, execution, observation, analysis and reflection. The subjects of this study were students of grade VI UPT SDN 1 Palapa, Tanjung Karang District, Bandar Lampung City Center. The data collection techniques used are test and non-test. While data analysis techniques are quantitative and qualitative discriptive analysis. The result of this study is the use of NHT type cooperative learning and the use of image media can improve social studies learning outcomes in grade VI students of UPT SDN 1 Palapa. This can be seen from the value of student learning outcomes during the learning process which is increasing. Grades before improvement showed that out of 28 students, only 10 students were complete (37%) and 18 students were incomplete (63%).After the actions taken, it can be seen that learning outcomes in the first cycle increased, from 28 students, 18 students who completed (67%) and 10 students who were not completed (37%). Learning outcomes in cycle II also increased. Of the 28 students, 25 students completed (89%) and 3 students who were incomplete (11%).